New Insights into the Synergistic Interaction Between Pseudomonas qingdaonensis NZ 1 and Silicon to Mitigate Drought Stress in Rice - Nazree Zainurin; Muhammad Imran; Shifa Shaffique; Muhammad Aaqil Khan; Sang-Mo Kang; Md. Injamum-UL-Hoque; Ashim Kumar Das; Byung-Wook Yun; In-Jung Lee (Microorganisms)
The current study assessed the synergistic effects of PGPR and Si in alleviating drought stress in rice. Bacteria were isolated from Phragmites australis inhabiting an urban riverbank. Among the isolated strains, Pseudomonas qingdaonensis NZ 1 showed promising results under in vitro drought stress induced by PEG-6000 (−0.28 MPa). To further investigate the synergistic effect of Pseudomonas qingdaonensis NZ 1 and silicon, a plant growth experiment was conducted comprising the control (dH2O) and plants treated with NZ 1, Si (1 mM), and NZ 1+Si under normal and drought stress conditions. The results revealed that NZ 1+Si-treated plants showed improved plant growth parameters, chlorophyll contents, relative water contents, antioxidant potential, and nutrient uptake under normal and drought conditions. Moreover, endogenous abscisic acid and jasmonic acid levels were substantially reduced, while the salicylic acid level was increased in NZ 1+Si-treated plants. Moreover, the relative expression of the ABA metabolic genes OsNCED3 and OsCYP707A6 and transcription factors OsbZIP23 and OsDREB1B were significantly altered. Furthermore, the leaf Si, calcium, potassium, and phosphorus contents were increased in NZ 1+Si-treated drought-stressed plants, along with the upregulation of OsLSi1. The combined application of NZ 1 and Si offers a sustainable agricultural strategy to effectively mitigate the detrimental effects of drought.